Practical and regulatory considerations for stability-indicating methods for the assay of bulk drugs and drug formulations - Kaufman, Teodoro Saul (2013)
As part of the overall analytical control strategy, current regulations require stability-indicating methods (SIMs) to demonstrate product integrity until the re-test period of drug substances (DSs) or throughout the shelf life of the drug products (DPs). Accordingly, relevant topics related to SIMs (mainly for DSs but also for DPs) are critically reviewed and some recommendations are given. The development of a SIM is a process that embraces three stages; these entail obtaining suitable samples, selecting the separation technique and choosing the right detection, which also comprises method development and optimization and, finally, validating the method. The first stage yields proper knowledge of the required physicochemical properties of the DS and a deep understanding of its intrinsic stability; these are acquired through stress and accelerated testing,an approach that provides the most appropriate samples for developing SIMs. For small organic molecules, HPLC is the first choice for undertaking the second stage, which entails developing powerful separations with stability-indicating properties. In case of biologics and certain combined products, achieving analytical methods with stability-indicating properties demands a series of methods based on different, orthogonal approaches. Adequate separation of the relevant degradation products from the main analytes requires optimization of a number of chromatographic factors, including column packing, mobile phase composition, the elution mode and other variables. Evaluation of all the stability-related issues demands proper detection systems. Sophisticated hyphenated chromatographic methods are extremely useful for developing powerful SIMs; however, similar chromatographic methodologies with simpler detections are enough for routine use of the SIMs as analytical tools. Full method validation according to official guides, and demonstration of suitability of the SIM for monitoring those products actually formed, finally proves its true stability-indicating power.